Strategi Layanan PUSPAGA sebagai One Stop Service Masalah Keluarga dan Anak di Lingkungan RW 02 Kelurahan Tanjungsari - Annisa Ika Putri; Vidya Imanuari Pertiwi (Public Inspiration : Jurnal Administrasi Publik, 2024)
Family problems often occur in society. The lack of parenting knowledge among parents and an environment that can make children uncontrolled are factors that cause violence in children. This is the government's focus on overcoming cases of family problems involving violence against women and children. One of the Surabaya City government pas through DP3APPKB to provide services for family problems is the PUSPAGA (Family Learning Center) services. This research aims to find out the strategy of the PUSPAGA services as a one-stop service for family and child problems in the RW 02 Tanjungsari Village environment. The research method used is qualitative descriptive research. The data source used is secondary data. Data collection techniques through observation and literature study from articles, materials, technical guidelines, and books related to this research topic. The results of the research show that the PUSPAGA services which was introduced in the smallest community environment, namely the RT/RW scope through PUSPAGA socialization activities provided new impacts and information on the community so that it could prevent and minimize family problems for women and children, especially in the RW 02 area of Tanjungsari Village